Pelatihan Branding dan Pemasaran Digital UMKM Kopi Kopisari di Desa Plaosan Kabupaten Malang - Elif, Nur; Dura, Justita; Cahyaningtyas, Fadilla; Andriany, Lussia Mariesti; Sidi, Agus Purnomo; Yogatama, Ahmad Nizar; Kabelen, Nicholaus Wayong; Ishak, Khairul Anuar bin; Mohidin, Mohd. Sahran @ Awang Bin; Suparman, Isyati Binti; Jaafar, Mime Azrina; Mustahidin, Nur Farhana Binti (Jurnal Pengabdian KOLABORATIF, 2026)
Kopisari Farmer Group manages a 0.29-ha coffee MSME in Plaosan Village with 360 BP 308 coffee trees planted since 2008. The main problems are the lack of clear brand identity, structured product narratives, and consistent digital marketing channel management. This community service program aims to improve the partner's branding and digital marketing capacity through hands-on training and mentoring. The method used is participatory training, including needs assessment, positioning-storytelling workshops, social media optimization practice, and content calendar development. The program was evaluated using pre-test and post-test methods. The results showed an 85% increase in partner understanding, with average scores rising from 40 to 85. Practically, the partner successfully produced a positioning document, brand identity draft, farm storytelling script, and content calendar. The partner also optimized their digital storefront and activated customer reviews as social proof. In conclusion, practice-based mentoring effectively accelerates digital marketing adoption for farmer-group-based coffee MSMEs
Keywords: Branding; Coffee MSME; Digital Marketing; Storytelling; Social Media